Somebody's awake - Rogers, Paul, 1950-; Corfield, Robin Bell (New York : Atheneum, 1989)
First up in the morning, a little boy gets his own breakfast and brings his parents a cup of tea.
13 18 31
Keywords: Breakfasts -- Fiction; Self-reliance -- Fiction; Morning -- Fiction